Pemberdayaan Kader Rumah Tangga Sebagai Strategi Pencegahan Penularan Covid 19 - Lestari, Ita Puji; Dewi, Maya Kurnia; Widyawati, Sigit Ambar (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2021)
Corona Virus Disease 2019 or COVID-19 is an infectious disease caused by SARS-CoV-2, a type of coronaviruses. People with COVID-19 may experience fever, dry cough, and difficulty breathing. The deaths recorded were 2,970 people and confirmed positive cases in Semarang were 677 people. The very fast transmission of COVID-19 has now become an issue that is being addressed globally, including in Indonesia. Based on the concept of handling health, the neglected problems are caused by ignorance, inability and unwillingness. To solve them, the activity for serving community was carried out. This activity consisted of the first stage by making a Covid-19 task force at RW level consisting of 15 people. The second stage was by increasing participants' understanding of foreign terms related to Covid-19 by 94.5%. The third stage of this activity was by gaining an understanding of the participants about the efforts to prevent Covid-19 at the household and community level by 87.5%. And the fourth stage was by getting an understanding of the Covid-19 vaccination by 81.25%. An effort to increase the role of the community in preventing Covid-19 is by doing similar activities periodically in the same location, therefore it can strengthen the community. An education about correct health information is important to be given to avoid misinterpretation.ABSTRAKCorona Virus Disease 2019 atau COVID-19 adalah penyakit menular yang disebabkan oleh SARS-CoV-2, salah satu jenis koronavirus. Penderita COVID-19 dapat mengalami demam, batuk kering, dan kesulitan bernafas. Jumlah kematian tercatat 2.970 orang dan kasus positif yang terkonfirmasi di Kota Semarang adalah 677 orang. Penularan COVID-19 yang sangat cepat kini telah menjadi isu yang sedang ditangani secara global termasuk di Indonesia.. Berdasarkan konsep penanganan kesehatan, bahwa terabaikannya permasalahan disebabkan oleh ketidaktahuan, ketidakmampuan dan ketidakmauan, maka kegiatan pengabdian ini dilaksanakan. Dari kegiatan pengabdian masyarakat ini, pada tahap pertama telah terbentuk sebuah kelompok satuan tugas penanganan Covid19 tingkat RW yang terdiri dari 15 orang. Pada tahap yang kedua, terdapat peningkatan pemahaman oleh peserta tentang istilah-istilah asing yang terkait dengan Covid 19 sebanyak 94,5%. Tahap ketiga kegiatan ini mendapatkan pemahaman tentang upaya pencegahan Covid19 pada tingkat rumah tangga dan masyarakat sebanyak 87,5%. Dan tahap yang keempat mendapatkan pemahaman tentang vaksinasi covid 19 sebanyak 81,25%. Dalam upaya lebih meningkatkan peran masyarakat dalam pencegahan Covid 19 maka kegiatan serupa perlu dilakukan secara berkala di lokasi yang sama, hal ini dapat menjadi upyaa penguatan di masyarakat. Edukasi kepada masyarakata tentang informasi kesehatan yang benar penting diberikan agar tidak menimbulkan pemahaman yang tidak diinginkan.